Temperature, OH and CH2O structure in the near field of oxy-fuel flames - Zulkifli, M; Beyrau, F; Williams, B (2017)
Oxygen-enhanced oxy-fuel flame structure in a co-flow non-premixed jet burner has been investigated. The effect of varying jet Reynolds number and O2 concentration on temperature and key species OH and CH2O was analysed. Temperature was measured using polarised/ depolarised (P/D) Rayleigh scattering and the OH/ CH2O species using planar laser induced fluorescence (PLIF), collected simultaneously. ‘Traditional Rayleigh’ requires a constant Rayleigh cross-section throughout the combustion process, which is impossible in high temperature oxy-fuel flames due to thermal decomposition leading to inaccuracy. However, a carefully-chosen combination of fuel and oxidiser can be exploited so the relative signal difference of P/D can be utilised. Mixture fraction can thereby be determined and temperature accurately recovered. This joint measurement enables combustion evolution in preheat (represented by CH2O) and oxidation (represented by OH) zones to be analysed. Detailed analysis of localised extinction was also performed.